2021
DOI: 10.3390/dj9110129
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and Its Role in Oral Diseases Development. Scoping Review

Abstract: Vitamin D is a fat-soluble secosteroid that plays a significant role in the whole body, including the maxillofacial region. The discovery of its receptors in many cells and organs made it possible to reveal the participation of vitamin D not only in the regulation of calcium phosphate metabolism, but also in immune processes, in providing anti-inflammatory and antimicrobial effects, slowing down cell proliferation and stimulating differentiation. In this literature review, we demonstrate the association betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 78 publications
0
22
0
2
Order By: Relevance
“…In 2020, Millen and Pavlesen reviewed studies that evaluated an association between vitamin D and periodontal disease; some prospective studies implied that vitamin D prevents tooth loss [ 55 ]. In a scoping review by Diachkova et al, some analyzed studies showed an association between low vitamin D levels and the severity of periodontal disease, defined as either lower soft tissue attachment/attachment loss, changes in probing depth, or reduced indications of systemic inflammation [ 56 ].…”
Section: Effects Of Vitamin D and Calcium Supplementation On Periodon...mentioning
confidence: 99%
“…In 2020, Millen and Pavlesen reviewed studies that evaluated an association between vitamin D and periodontal disease; some prospective studies implied that vitamin D prevents tooth loss [ 55 ]. In a scoping review by Diachkova et al, some analyzed studies showed an association between low vitamin D levels and the severity of periodontal disease, defined as either lower soft tissue attachment/attachment loss, changes in probing depth, or reduced indications of systemic inflammation [ 56 ].…”
Section: Effects Of Vitamin D and Calcium Supplementation On Periodon...mentioning
confidence: 99%
“…Лиганды VDR активируют деятельность N-киллеров, расположенных в полости рта, и увеличивают фагоцитарную активность макрофагов [45]. Регуляция неспецифического иммунного ответа происходит за счет стимуляции синтеза антимикробных пептидов (β-дефенсинов и кателицидинов) через рецепторы витамина D. В ответ на антигенную стимуляцию активированные клетки врожденного иммунитета продуцируют антимикробные агенты [19]. 1,25(OH) 2 D индуцирует экспрессию β-дефензинов, участвующих в формировании иммунной устойчивости тканей полости рта к микробной колонизации, в том числе пародонтопатогенных штаммов, таких как Actinobacillus actinomycetemcomitans, Porphyromonas gingivalis, Fusobacterium nucleatum, Candida [53,54].…”
Section: влияние колекальциферола и его активных метаболитов на регул...unclassified
“…Работы зарубежных и отечественных авторов показывают, что дефицит витамина D влияет на одонтогенез, в результате чего возникает гипоминерализация твердых тканей зубов, как следствие, увеличение риска возникновения и прогрессирования кариеса зубов, гипоплазии эмали [14,16]. Недостаток витамина D влияет на развитие ответной иммунной реакции при воспалительном процессе в полости рта [14,17,18], ремоделирование костной ткани челюстей [14,19] и формирование противоопухолевого эффекта в тканях челюстно-лицевой области [14,19,20].…”
unclassified
“…The potential benefits of adequate vitamin levels include, but are not limited to reduced risk for neurodegenerative disorders, infections, heart failure, stroke, cardiovascular disease, diabetes, cancer, autoimmune diseases, and infections [2,6,83]. In the oral cavity, vitamin D insufficiency has been linked to higher risk for chronic periodontitis, recurrent aphthous stomatitis, oral cancer, caries, and defective tooth mineralization, with potential effects on orthodontic tooth movement, and dental implant osseointegration and BIC [13,54,61,84].…”
Section: Supplementationmentioning
confidence: 99%